Does happiness increase in old age?: Longitudinal evidence from 20 European countries [dataset] - Becker, Christoph; Trautmann, Stefan T. (Universität, 2022)
Several studies indicate that happiness follows a U-shape over the life cycle: Happiness decreases after the teenage years until reaching its nadir...